EFEKTIVITAS STRATEGI PEMASARAN MELALUI INSTAGRAM DALAM MENINGKATKAN KUNJUNGAN PASIEN LAMA DAN BARU KE RUMAH SAKIT - Nurlatifah Rahmayanti; Farida Yuliaty (STKIP Subang, 2024)
This study aimed to analyze the effectiveness of using social media, particularly Instagram, in increasing hospital patient visits through a literature review approach. Social media has become a crucial tool in hospital digital marketing strategies, especially in building engagement with users. The analysis was conducted by reviewing several relevant journals that discuss the impact of digital marketing strategies on user engagement and patient visits. The analysis results showed that attractive visual content, consistent posting frequency, and active user interaction can significantly enhance engagement, which in turn leads to an increase in patient visits, both new and returning patients. Additionally, hospitals that utilize social media as a platform for health education successfully build public trust. In conclusion, social media marketing strategies are effective in expanding audience reach and increasing patient visits; however, managing interactions and regular evaluations are key factors that need to be considered to maintain long-term success.